Using Local Language in Traditional Market between Sellers and Buyers - Ulik, Farras Dwi Farhani; Nuryanti, Dewi (ESENSI LINGUA, 2023)
This research focuses on language variations in buying and selling transaction process at the Embrio Traditional Market located in Kecamatan Makasar, East Jakarta City. This research aims to identify and describe the types of language variations found in interactions between buyers and sellers at the Embrio Traditional Market and describe the factors underlying the use of language variations. The theory used to analyze the data in this study is the theory from Janet Holmes (2017) regarding the use of dialect and the background of the occurrence of language variations, Martin Joos in Naibaho (2020) the variety of languages in terms of formality, and the theory from PWJ Nababan in Naibaho (2020) the variety of languages in terms of utilization. The results of this study are the first (1) to use types of language variations including: the use of dialects, such as Sundanese, Betawi, and Javanese dialects; language variations in terms of utilization, namely use in the economic field; and language variations in terms of formality, namely consultative variety, casual variety, and intimate variety. The second (2) result is the reasons behind the occurrence of language variations, there are the similarity of ethnic background, negotiation strategies, and to attract buyers.